PENGARUH EDUKASI GIZI BERBASIS MEDIA INSTAGRAM TERHADAP TINGKAT PENGETAHUAN GIZI SEIMBANG DAN ASUPAN ZAT GIZI MAKRO REMAJA DI SMAN 01 NGABANG - Tiara Sani Yulianti; Suaebah; Jonni Syah R Purba purba (Media Gizi Khatulistiwa, 2025)
Adolescence is a transition to adulthood. A lack of nutritional knowledge can cause various health problems. The prevalence of very thin and thin nutritional status in adolescents in West Kalimantan is increasing, with the latest figures being 1.4% very thin and 5.6% thin. In Landak Regency, the prevalence of very thin is 6.6%, and thin is 2.6%, higher than the national average. Nutrition education through Instagram, which is used by 42.3% of teenagers, can be an effective solution to this problem. This study aims to determine the impact of nutrition education through Instagram media on teenagers' knowledge of balanced nutrition and macronutrient intake. The research method involved conducting a pre-experiment with a sample of 38 respondents. Random sampling was used as the sampling technique. Data analysis using the Wilcoxon signed-rank test for non-normally distributed data and the paired t-test for normally distributed data. After education, there was an increase in knowledge of 1.32 points, as well as an increase in energy intake of 912.12 grams, carbohydrates 79.1 grams, protein 8.5 grams, and fat 12.15 grams, with a p-value of 0.000 (p <0.05). This study demonstrates the impact of Instagram media on teenagers' knowledge of balanced nutrition and macronutrient intake, both before and after receiving education.